Atmospheric pressure field desorption-trapped ion mobility-mass spectrometry coupling - Gross, Jürgen H. (Analytical and bioanalytical chemistry, 2024)
While field ionization (FI) and field desorption (FD) are established soft vacuum ionization methods in mass spectrometry (MS), the technique of atmospheric pressure field desorption (APFD) has only recently been added to the repertoire. Similar to FI and FD, APFD can yield both positive even-electron ions of highly polar or ionic compounds and positive molecular ions, M+•, e.g., of polycyclic aromatic compounds. Thus, a dedicated APFD source assembly has been constructed and demonstrated to allow for robust APFD operation. This device also enabled observation of the emitter during operation and allowed for resistive emitter heating, thereby speeding up the desorption of the analytes and expanding the range of analytes accessible to APFD. While initial work was done using a Fourier transform-ion cyclotron resonance (FT-ICR) mass spectrometer, the new APFD source offered the flexibility to also be used on a trapped ion mobility-quadrupole-time-of-flight (TIMS-Q-TOF) instrument, and thus, it would be possible to be mounted to any Bruker mass spectrometer featuring an atmospheric pressure (AP) interface. Operating an APFD source at a TIMS-Q-TOF instrument called for the exploration of the combined use of APFD and TIMS. Here, operation, basic properties, and capabilities of this new atmospheric pressure field desorption-trapped ion mobility-mass spectrometry (APFD-TIMS-MS) coupling are described. APFD-TIMS-MS is employed for the separation of individual components of oligomers and for the accurate determination of their collision cross section (CCS). This work describes the application of APFD-TIMS-MS on poly(ethylene glycol) forming [M + Na]+ ions by cationization and on an amine-terminated poly(propylene glycol) yielding [M + H]+ ions. Some compounds forming molecular ions, M+•, by field ionization such as [60]fullerene and a mixture of four polycyclic aromatic hydrocarbons (PAHs) are examined. In APFD-TIMS-MS, the limits of detection (LODs) of fluoranthene and benzo[a]pyrene M+• ions are determined as ≈100 pg and <1 pg, respectively. Finally, [60]fullerene is analyzed by negative-ion APFD-TIMS-MS where it yields a molecular anion, M−•.